Families of the forest : the Matsigenka Indians of the Peruvian Amazon - Johnson, Allen W. (Hellenistic culture and society ;, 2003)
The idea of a family level society assumes moving, breathing form in Families of the Forest. According to Allen Johnson's ethnography, the Matsigenka people of southeastern Peru cannot be understood or appreciated except as a family level society; the family level of sociocultural integration is for them a lived reality.